Sharia-Based Teachers’ Strategies In Teaching The Concept Of Money And Saving To Early Childhood Students At Tadika Tahfiz Nur Furqan, Malaysia - Annisa Dwi Rani (International Conference on Islamic Economic (ICIE), 2026)
This study addresses the limited integration of Islamic financial literacy in early childhood education, particularly in cultivating foundational understanding of money and Sharia-based saving habits. It aims to analyze teachers’ strategies in teaching the concept of money and Islamic-oriented saving behavior to young learners at Tadika Tahfiz Nur Furqan. The research employs a descriptive qualitative approach, with data collected through classroom observations, semi-structured interviews, and documentation analysis. The findings reveal that teachers apply play-based learning strategies, including simulations of buying and selling activities, structured daily saving routines, and the integration of Islamic values such as trustworthiness (amanah), honesty (ṣidq), thriftiness (iqtiṣād), and social responsibility. The implementation of a routine saving program enables children to understand the basic functions of money while gradually shaping responsible economic behavior grounded in Islamic principles. Furthermore, active parental involvement reinforces the consistency of saving practices at home. This study contributes to the development of a Sharia-based financial literacy model for early childhood education through contextual learning and systematic habit formation rooted in Islamic values.